Animal Images in Shamanic Cult and Attributes in Traditional Yakut Culture - Aitalina R. Fedorova; Svyatoslav I. Fedorov (Гуманитарный вектор)
The purpose of this article is to systematize and define the role of the animal world in the mythology of Yakut shamanism and its attributes. The topic of shamanism was studied earlier mainly from an anthropocentric point of view. At present, it is interesting to consider the role of animal images in the shamanic cult and the way their communication with the shaman takes place. The sources of the study were archival and published ethnographic and folklore materials on traditional Yakut beliefs. With their help the plots in which animals appear as patron spirits, spirit-helpers and symbolic images were revealed. The animal image of the shamanic patron spirit – “iye-kyyl” (mother-beast) which participates in the “birth” of the shaman was considered. We also paid attention to animals acting as helper spirits directly in contact with the shaman: they ensure his mobility in supernatural spaces and share their powers and abilities with him. The material use of animal images for magical and apotropaic purposes in the shaman’s paraphernalia is touched upon. The methodological basis of the study is the actor-network theory and the symbolic approach. As a result of the study, we conclude that in Yakut shamanism animal images play a significant role of intermediaries between shamans and supernatural spaces. The study reveals the ideas that spirits act in an active capacity: they do not simply carry functional roles, but are themselves the initiators of the supernatural spaces.